Desenvolvimento de sensor nanomecânico de cantilever para detecção de micrornas marcadores de metástases de carcinoma epidermóide de cabeça e pescoço (CECP) - Andrade, Mariana Arnaud de (Universidade Federal de São Carlos, 2018)
Head and neck squamous cell carcinoma (HNSCC) is a neoplasm that affects the regions of the oral cavity, pharynx and larynx with high incidence, reaching approximately 600 thousand new cases per year. Cases of local recurrence and distant metastases after treatment are common and decrease the rate of overall survival for patients with HNSCC, culminating in increased mortality rates, which have not improved for 40 years. The use of molecular markers, such as microRNAs, has been widely approached by the scientific community as a promising new methodology for tumor detection. This work aimed to the development of a genossensor with microlevels (cantilevers) of Atomic Force Microscopy (AFM) for analysis and detection of miRNA markers (miR-203 and miR-205) for the study of cervical lymph node metastasis. The genossensor was developed from the functionalisation process, which consists of the chemical modification of the surfaces of the microalvans, so that the complementary tapes of the miRNAs markers are immobilized and subsequently detect their target. Results obtained indicate that the proposed functionalization methodology was efficient, and confirmed the immobilization of the complementary tapes of the miRNAs markers, from the characterization by Fluorescence Microscopy and AFM morphological images. Detection of both miR-203 and miR-205 markers varied according to the different concentrations studied (100, 120, 140 and 160 nM). Through the developed genossensor it was possible to detect the target molecules: for the miR-203 marker, 10 to 72 nm cantilever deflection data were obtained, as well as for the miR-205 marker the deflection data from 10 to 170 nm. The innovative character of this work is contained in the development of a new methodology for the detection of metastasis, which, a priori, uses synthetic samples of HNSCC metastasis markers, but in the future it may be applied to real samples of patients affected by such pathology.
Development of a nanomechanical cantilever sensor for the detection of markers of metaphors of squamous cell carcinoma of the head and neck (HNSCC)
Keywords: Nanomechanical Cantilever Sensors; Head and neck squamous cell carcinoma; MicroRNAs; Microscópio de Força Atômica; Sensores Nanomecânicos de Cantilever; Carcinoma Epidermoide de Cabeça e Pescoço; Metástases; Atomic Force Microscope; CIENCIAS BIOLOGICAS::BIOFISICA